Personal and community values behind sustainable food consumption: a meta-ethnography - Lamarque, Muriel; Tomé-Martín, Pedro; Moro-Gutiérrez, Lourdes (Frontiers in Sustainable Food Systems, 2023)
Various aspects of sustainable food consumption have been studied within the Social Sciences in the last years. Specifically, the analysis of motivations and determinants behind alternative economic practices has gained prominence in disciplines such as Sociology, Psychology, Economics and Marketing, seeking to understand, measure and calculate consumers’ decision-making processes and actions through the application of cognitive theories and qualitative predictive models. Anthropology—more specifically through the practice of ethnography—, has also made significant contributions, mostly toward the analysis and description of contemporary cooperative experiences, both in rural and urban settings. However, within this field, few studies have focused on the underlying values, as well as the symbolic, emotional/affective, and identity-based incentives that exist behind the participation in sustainable, pro-environmental, organic, and fair-trade food initiatives. This kind of perspective might help in comprehending how different people or social groups conceptualize their habits and link them to certain representations or beliefs. At the same time, it can provide information about the way in which action-related values appear in discourse and become embodied, whether they are uniform, conflicting, precede practice or emerge as a post-personal reflection of those involved. Through a review, synthesis, and analysis of qualitative literature—meta-ethnography—this paper seeks to present an overview of available academic work on the social, political, personal, material, and ethical reasons associated with partaking in alternative food networks. The findings will be analyzed and discussed in relation to a constructivist perspective, as well as debates around identity, social distinction, and gender.